Refinancing cross-subsidies in the mortgage market - Fisher, Jack; Gavazza, Alessandro; Liu, Lu; Ramadorai, Tarun; Tripathy, Jagdish (Journal of Financial Economics, 2024)
In household finance markets, inactive households can implicitly cross-subsidize active households who promptly respond to financial incentives. We assess the magnitude and distribution of cross-subsidies in the mortgage market. To do so, we build a structural model of household mortgage refinancing and estimate it on rich administrative data covering the stock of outstanding mortgages in the UK. We estimate sizeable cross-subsidies that flow from relatively poorer households and those located in less-wealthy areas towards richer households and those located in wealthier areas. Our work highlights how the design of household finance markets can contribute to wealth inequality.